QUALITATIVE CHARACTERISTIC OF FORAGE OF BIRD'S-FOOT-TREFOIL CULTIVARS (LOTUS CORNICULATUS L.), GROWN IN THE REGION OF TROYAN (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The chemical composition of following bird's foot-trefoil cultivars was evaluated: 'Bright', 'Georgia 1' (USA), 'Nueltin' (USA), 'Witt', 'Pardee' (USA), 'Roseau' (USA), 'Steadfast', 'Trevig' (USA), harvested in the experimental field of RIMSA-Troyan during the period of 2010/2012. The indicators for crude protein, crude fat, crude fiber, nitrogen-free extractable substances (NFE), calcium and phosphorus were followed. The correlation dependences among them, the yield and morphological composition of grassland were calculated. After their statistical processing and comparative assessment was found the variability among cultivars according to undergrowths. Very low variability (VC) was registered regarding the content of crude protein (6.51 and 8.44), crude fiber (3.38 and 5.58), nitrogen-free extractable substances (5.02 and 3.46), ash (5.06 and 2.69) and it was low for calcium (10.97 and 7.99) and phosphorus (5.52 and 12.53). Genotypes of 'Trevig' and 'Pardee' cultivars were outlined as the most perspective for use in the selection programmes and for introduction in production under specific soil and climate conditions. 'Trevig' cultivar especially distinguished itself as it combined high content of protein (179.0 and 210.9 g kg-1) and low content of crude fiber (268.7 and 277.3 g kg-1). The strong positive correlation between content of crude protein and the relative share of leaves in the grassland (r=0,796); the content of crude fiber and height of plants (r=0,605); generative organs and content of calcium (r=0,597), which were found, showed that these features were interrelated.